The pass-through to inflation of gas price shocks - Lucia López; Florens Odendahl; Susana Párraga Rodríguez; Edgar Silgado-Gómez (European Central Bank (ECB), 2024)
This paper uses a Bayesian Structural Vector Autoregressive (BSVAR) framework to estimate the pass-through of unexpected gas price supply shocks on HICP inflation in the euro area and its four largest economies. In comparison to oil price shocks, gas price shocks have approximately one-third smaller pass-through to headline inflation. Country-specific results indicate gas price increases matter more for German, Spanish and Italian inflation than for French inflation, hinging on the reliance on energy commodities in consumption, production, and different electricity prices regulation. Consistent with gas becoming a prominent energy commodity in the euro area, including time-variation through a time-varying parameter BVAR demonstrates a substantially larger impact of gas price shocks on HICP inflation in recent years. The empirical estimates are then rationalized using a New Keynesian Dynamic Stochastic General Equilibrium (NK-DSGE) model augmented with energy. In the model, the elasticity of substitution between gas and non-energy inputs plays a critical role in explaining the inflationary effects of gas shocks. A decomposition of the recent inflation dynamics into the model structural shocks reveals a larger contribution of gas shocks compared to oil shocks.
Keywords: C11; C32; E31; Q41; 330; Natural gas and oil shocks; Inflation; Bayesian VARs; New Keynesian DSGE